1995
DOI: 10.1007/bf00052179
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, medical history, and risk of testicular cancer (Alberta and British Columbia, Canada)

Abstract: In order to evaluate risk factors for germ cell cancers, we conducted a case-control study of 510 men with testicular cancer aged 15 to 79 years and 996 randomly selected age-matched controls in the provinces of British Columbia and Alberta, Canada. Subjects completed a mailed questionnaire providing data on education level, ethnic origin, medical history, smoking, occupation, and recreational and sports activity. The response rate among cases was 80.3 percent and among controls was 68.1 percent. After control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
79
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 28 publications
(1 reference statement)
2
79
0
Order By: Relevance
“…The results of the present evaluation are in line with seven previous studies (Kleinteich and Marx, 1983;Gallagher et al, 1995;Dieckmann and Pichlmeier, 2002;Rasmussen et al, 2003;Richiardi et al, 2003;Hardell et al, 2006;McGlynn et al, 2007) encompassing 3098 patients. Nine other studies had failed to demonstrate a significant correlation of body size with GCT risk (Whittemore et al, 1984;Swerdlow et al, 1989;Thune and Lund, 1994;UK Testicular Cancer Study Group, 1994;Davies et al, 1990Davies et al, , 1996Petridou et al, 1997;Bjørge et al, 2006;Stang et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present evaluation are in line with seven previous studies (Kleinteich and Marx, 1983;Gallagher et al, 1995;Dieckmann and Pichlmeier, 2002;Rasmussen et al, 2003;Richiardi et al, 2003;Hardell et al, 2006;McGlynn et al, 2007) encompassing 3098 patients. Nine other studies had failed to demonstrate a significant correlation of body size with GCT risk (Whittemore et al, 1984;Swerdlow et al, 1989;Thune and Lund, 1994;UK Testicular Cancer Study Group, 1994;Davies et al, 1990Davies et al, , 1996Petridou et al, 1997;Bjørge et al, 2006;Stang et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The indication of a raised risk of testicular cancer in taller twins accords with evidence in this direction, but not strong, from four case-control studies of unrelated subjects (Brown et al, 1987;Swerdlow et al, 1989;UK Testicular Cancer Study Group, 1994;Gallagher et al, 1995), although not a fifth (Davies et al, 1990). A cohort study with fewer cases reported no association but did not publish further details (Whittemore et al, 1984).…”
Section: Discussionmentioning
confidence: 73%
“…These factors could not, however, explain the results. Age at onset of puberty (37) and trauma or injuries (32,38) have been suggested to influence the cancer risk. Our finding was neither associated with onset of puberty nor disciplines closely to trauma or injuries.…”
Section: Discussionmentioning
confidence: 99%